Isotopic evidence of passive mineral carbonation in mine wastes from the Dumont Nickel Project (Abitibi, Quebec). (May 2017) - Gras, A.; Beaudoin, G.; Molson, J.; Plante, B.; Bussière, B.; Lemieux, J.M.; Dupont, P.P.
Highlights: Natural weathering of ultramafic mining residues sequesters carbon dioxide. Main evidence is low CO2 concentration, carbon content increase and carbonate precipitation. CO2 dissolution induces a 13 C enrichment of pore gas and 13 C depletion in carbonate minerals. The source of CO2 sequestered is determined using isotope geochemistry. A conceptual model of mineral carbonation including isotope geochemistry is proposed. Abstract: Natural weathering of ultramafic rocks in mine tailings captures atmospheric CO2 through the formation of magnesium carbonates. The Dumont Nickel Project (DNP) is of particular interest as it will generate 1.7 Gt of ultramafic residues. A field experiment has been conducted at the DNP site in order to understand the process of natural CO2 sequestration. Two experimental cells were built using waste rock and mineral processing tailings and were instrumented with gas sampling ports and probes to monitor water saturation and suction. A decrease of the interstitial gas-phase CO2 concentration in both cells, from atmospheric values (∼390 ppmv) near the surface to ∼100 ppmv near the bottom, reflects active CO2 consumption by the residues. The total carbon content of the weathered DNP mine waste ranges from 0.2 wt% to 6.5 wt% C. Hydrotalcites supergroup minerals (pyroaurite-3R, brugnatellite, pyroaurite 2-H), aragonite, nesquehonite, dypingite and hydromagnesite were absent from the unweathered residues and precipitated in the cells during passive mineral carbonation. In situ measurements using Wavelength-Scanned Cavity Ring Down Spectroscopy reveal an increase of δ 13 C(air) from −8‰ near the surface of the cells to ∼2‰ near the bottom that is correlated with the decrease in CO2 concentration. This trend is explained by kinetic carbon isotope fractionation during dissolution of atmospheric CO2 in interstitial water (ΔDIC-CO2  = −11.2‰). Secondary carbonates, precipitated from the interstitial water, are characterized by a moderately high δ 18 O and low δ 13 C. These isotopic compositions of the carbonates are consistent with precipitation in an evaporative environment where the kinetic carbon fractionation during atmospheric CO2 dissolution produces interstitial water depleted in 13 C. Moreover, isotopic compositions of hydrotalcite supergroup minerals and other carbonate minerals are consistent with modern precipitation from the weathering of mining residue. These observations demonstrate the atmospheric source for the sequestered CO2 and help constrain a conceptual model of the carbonation reaction in the residues.